Factors Affecting Character Formation: Discipline, Counseling Guidance, and Sports Education - Muliawan, Adi (Dinasti Research, 2021)
Literature review factors in character formation: discipline, counseling guidance, and sports education are scientific articles aimed at analyzing whether character formation is influenced by discipline, counseling guidance, and sports education. The method approach is qualitative with a descriptive study type (literature review) to explore and analyze the relationship between discipline, counseling guidance, sports education, and character formation. The results of this article are: 1) Discipline plays a role in character formation; 2) Counseling guidance plays a role in character formation; 3) Sports education plays a role in character formation. In addition to these 3 exogenous variables affecting the endogenous variable of character formation, there are many other factors including the quality of education, physical activity, and leadership.